Early re-suturing of dehisced obstetric perineal wounds: A 13-year experience. (November 2020) - Okeahialam, NA; Thakar, R; Kleprlikova, H; Taithongchai, A; Sultan, AH
Abstract: Objectives: To describe post-operative outcomes following early re-suturing of obstetric perineal wound dehiscence. Study Design: This was a retrospective series of 72 women who underwent re- suturing of a dehisced perineal wound at a tertiary urogynaecology department during a 13-year period (December 2006 - December 2019). Results: Seventy-two women with complete perineal wound dehiscence opted for secondary re-suturing. Other accompanying symptoms included purulent discharge from the wound (22.2 %), perineal pain (23.6 %) and both purulent discharge and pain (26.4 %). The median time taken for the wound to heal completely following re-suturing was 28 days (IQR 14.0-52.0); 49.2 % had healed completely by four weeks, 63.5 % by six weeks and 76.2 % by eight weeks. The median number of out-patient follow-up appointments required was 2 (IQR 1.0-3.0). No post-operative complications were experienced in 63.6 % of women, one complication occurred in 25.8 % and two complications in 10.6 %. Complications included skin dehiscence (33.3 %), granuloma (33.3 %), scar tissue (17.6 %), perineal pain (5.9 %) and sinus formation (5.9 %). Of the women who developed two complications, four developed skin dehiscence with granulation tissue and one had skin sinus formation. One developed granulation tissue with perineal pain. All complications were managed conservatively in an outpatient setting or surgically under local anaesthetic, without further complication. There was no significant difference (p = 0.443) in complication rates between the group (n = 10) with dehisced wounds with signs of wound infection (purulent discharge or the presence of both purulent discharge and pain) pre-operatively versus the group (n = 14) without signs of infection. Conclusions: This study demonstrates the positive outcomes of early re-suturing of perineal wound dehiscence with faster healing, reduced follow-up requirements and few major complications. It provides information to clinicians who are uncertain about the effects of early re-suturing of perineal wounds which can be used to help counsel mothers with wound dehiscence on their management options.